A formação Sopa-Brumadinho nos campos diamantíferos de São João da Chapada, Sopa-Guinda e Extração, Diamantina - Márcio Célio Rodrigues da Silva (2016)
Studies developed in diamond deposits in São João da Chapada, Sopa-Guinda and Extração, in the Diamantina region, Minas Gerais, focusing the Sopa-Brumadinho Formation, Espinhaço Supergroup, have shown that the apparently complex siliciclastic lithofacies arrangements may be organized and better understood when they are interpreted in the light of sequence stratigraphy concepts developed for rift basins, especially stacking patterns and tectonic system tracts adjusted in half-grabens. The coarsening-upward stacking pattern involving pelites at the base, a lacustrine depositional system marking the rift start tectonic tract, with intermediate sandstone related to braided river systems, that are consistent with the half-graben development tectonic tract, overlapped by fan-deltaic alluvial fans associate to the rift climax tectonic tract, make up a logical and coherent frame for understanding the multiplicity of aspects that characterize this lithostratigraphic unit. The succession top consists of pelites, setting a coastal onlap, marking a fining-upward interval, which record the transition from a continental environment, whose sedimentation was controlled by the tectonic, to a shallow marine environment, controlled by eustatic variation. The contributions resulting from synsedimentary magmatism constitute an important attribute of this unity, notedly in the form of volcaniclastic and epiclastic products. Fine tuff and lapilitic tuff intercalations were characterized in São João da Chapada, subvolcanic dikes in the Sopa-Guinda and Extração fields, as well as the general contamination of sediments by igneous material, possibly volcanic ashes, was characterized in the three fields, evidenced by the geochemical signatures of these rocks based on low geochemical mobility trace element diagrams and rare earth elements. Such signatures indicate that magmatism contemporaneous to sedimentation has been predominantly acid, rhyolitic, subordinately intermediate, trachyandesite, and, occasionally, basic and alkali basalt. The characterized lithofacies was interpreted as a clay matrix breccia with angular clasts, exclusively red quartzite, as being of volcanoclastic nature, originating from phreatic eruption explosive processes, affecting an oxidized zone, by exclusive action of gases and steam heated by deep magma chamber. Geochronological studies, using the LA-MC-ICP-MS U/Pb method, in detrital and igneous zircon in São João da Chapada and Sopa-Guinda fields support the interpretation that the Sopa-Brumadinho Formation sediments in these areas have minimum age of 1.70 Ga, defined based on the acid intrusion crystallization in sandstone from the half-graben tectonic tract, and that the sedimentation period is included between 1.74 and 1.68 Ga, with imprecise upper limit, after the end of São João da Chapada Formation sedimentation (1.79-1.76 Ga) and subsequent period of this unit's erosion (1.76-1.74 Ga). At the Extração field, sedimentation would be comprised approximately between 1.64 Ga, age of the basic intrusion crystallization that cuts sandstone-underlapping conglomerates, and 1.60 Ga. This lower limit may be even later, as it has been associated to detrital zircon in conglomerate matrix, whereas the upper limit may be older, as this is the minimum age. This statement enables concluding that tectonic and sedimentary evolution in this field was not synchronous to the others, in a broader system, which enables a thicker sedimentation in larger tectonic compartments, evidencing the rift's propagation direction as East and South. In terms of origin, based on the studies of zircons found in this unit's rocks, extracted from conglomerate and volcaniclastic matrices, it has been concluded that the greatest contribution originates in the rhyacian period (2.30-2.05 Ga), with approximately 70% of dated zircons, followed by the mesoarchean grounds (3.2-2.8 Ga - 18%), orosirian (2.05-1.80 Ga - 6%), staterian (1.80-1.60 Ga - 2%) and paleoarchean (3.60-3.20 Ga - 1%). Isotopic studies using the Lu/Hf system in zircons dated by U/Pb extracted from acid and basic intrusion rocks have shown, based on the negative epsilon Hf of staterian zircons, that these minerals have crystallized as magma originating from crustal sources, thus weakening the hypothesis of an autochtonous origin for diamonds in the Southern Espinhaço range. The use of trace elements of low geochemical mobility, by the ratio Nb/Y versus Zr/Ti, plotted in Winchester & Floyd diagram (1977), combined with the Rare Earth Elements standards, has highlighted the signature of the magmatic rocks inserted in metassedimentary rocks of Sopa-Brumadinho Formation, that were changed by metamorphism and/or hidrothermalism and weathering. Acid to intermediate tuffs prevailed in São João da Chapada field, acid dykes and tuffs in Sopa-Guinda field, and intermediate to basic dykes and tuffs in Extração field.